Health safety in wastewater reuse in irrigated agriculture - Pereira L.S. (Non-conventional water use: WASAMED project, 2005)
Literature is abundant on wastewater reuse in agriculture but are quite limited the studies concerning safety issues to minimise the health risk from using wastewater in irrigation. Based upon a Unesco book produced by the author where these subjects are treated, main issues to favour health safety of consumers, farmers and other agents are discussed herein. Thus, a review is presented focusing on health concerns, the need to better consider about the need for more stringent water treatments, the suitability of irrigation methods, the need to apply crop restrictions when wastewater contamination hazards are not avoidable, the need to consider the promotion of safe crop production areas, and the consequent requirements for monitoring and control, which may lead to the certification of products, producing areas and farmers. The presentation mainly aims at provoking a discussion on such issues and using a few positive case studies in the Mediterranean area.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)